2010
DOI: 10.1038/cmi.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 signaling in host defense and inflammatory diseases

Abstract: Interleukin (IL)-17, the signature cytokine secreted by T helper (Th) 17 cells, plays important roles in host defense against extracellular bacterial infection and fungal infection and contributes to the pathogenesis of various autoimmune inflammatory diseases. Here we review the recent advances in IL-17-mediated functions with emphasis on the studies of IL-17-mediated signal transduction, providing perspective on potential drug targets for the treatment of autoimmune inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 71 publications
(76 reference statements)
0
62
0
2
Order By: Relevance
“…In a coculture assay of purified MAIT cells and mycobacterium-infected M⌽, MAIT cells were found to curtail growth of intracellular bacterial replication associated with the secretion of IFN-␥ and IL-17A, known mediators of immunity against intracellular and extracellular bacterial infection (17,19,22,42,47,63,80). Furthermore, the "first-line" production of IFN-␥ and IL-17A by innate lymphocytes is known to play an important role in bridging innate and adaptive immunity (3,21,36,46,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…In a coculture assay of purified MAIT cells and mycobacterium-infected M⌽, MAIT cells were found to curtail growth of intracellular bacterial replication associated with the secretion of IFN-␥ and IL-17A, known mediators of immunity against intracellular and extracellular bacterial infection (17,19,22,42,47,63,80). Furthermore, the "first-line" production of IFN-␥ and IL-17A by innate lymphocytes is known to play an important role in bridging innate and adaptive immunity (3,21,36,46,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of IL-17 and its biological functions, many studies have demonstrated that increased IL-17 expression is associated with inflammatory autoimmune diseases in either human patients or animal disease models [137,174,175]. Robust evidence shows that IL-17 mediates adverse effects in many autoimmune diseases such as RA, MS, SLE, IBD (inflammatory bowel disease) and psoriasis to name a few [176].…”
Section: Pathological Roles Of Il-17 In Autoimmune Diseasesmentioning
confidence: 97%
“…More IL-17-producing sources have now been found, especially innate immune cells (6,23). IL-17 belongs to a cytokine family containing six members (IL-17A to IL-17F) which are structurally different from other cytokines (7,8,16,26,40). IL-17 is the best-characterized member of the family.…”
mentioning
confidence: 99%
“…IL-17 is the best-characterized member of the family. IL-17 is a proinflammatory cytokine and acts on local tissue cells to induce production of genes for proinflammatory proteins, including cytokines, chemokines, and matrix metalloproteases, to amplify inflammation (8,16,26). The IL-17 level is elevated in a variety of inflammatory and autoimmune disorders, while IL-17 deficiency or its functional blockage reduces the development and pathogenesis of autoimmune diseases, suggesting that IL-17 is a promising target for various inflammatory disorders (16,26).…”
mentioning
confidence: 99%